2004
DOI: 10.1523/jneurosci.2079-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mapping of the Auditory Midbrain during Mate Call Reception

Abstract: We examined patterns of neural activity as assayed by changes in gene expression to localize representation of acoustic mating signals in the auditory midbrain of frogs. We exposed wild-caught male Physalaemus pustulosas to conspecific mating calls that vary in their behavioral salience, nonsalient mating calls, or no sound. We measured expression of the immediate early gene egr-1 (also called ZENK, zi/268, NGFI-A, and krox-lA) throughout the torus semicircularis, the auditory midbrain homolog of the inferior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 53 publications
10
82
1
Order By: Relevance
“…In addition, the increase in firing rate continued past the stimulus presentation leading to the conclusion that acoustic stimulation acts as a modulator of ongoing activity within central endocrine control areas (Allison, 1992). Although neurophysiological work has not been done in túngara frogs, Hoke et al (2004Hoke et al ( , 2005 demonstrated midbrain activation and hypothalamic sensitivity to conspecific calls in this species using immediate early gene activation. Increases in neural activity within the central endocrine regions translate into elevated gonadal steroid concentrations in male anurans (Burmeister and Wilczynski, 2000;Chu and Wilczynski, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increase in firing rate continued past the stimulus presentation leading to the conclusion that acoustic stimulation acts as a modulator of ongoing activity within central endocrine control areas (Allison, 1992). Although neurophysiological work has not been done in túngara frogs, Hoke et al (2004Hoke et al ( , 2005 demonstrated midbrain activation and hypothalamic sensitivity to conspecific calls in this species using immediate early gene activation. Increases in neural activity within the central endocrine regions translate into elevated gonadal steroid concentrations in male anurans (Burmeister and Wilczynski, 2000;Chu and Wilczynski, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm mate receptivity, each female was tested once by using standard phonotaxis tests with whine and whine-chuck stimuli broadcast at 82 dB SPL (sound pressure level, relative to 20 P) from speakers at opposite sides of an acoustic chamber, then responsive females were placed inside sound-dampening boxes. After 2 h without stimulation, we exposed females to one of five acoustic treatments as described (30): silence, natural heterospecific P. enesefae call, natural P. pustulosus whine, natural P. pustulosus whine-chuck, or P. pustulosus chuck trimmed from the whine-chuck stimulus (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…We exposed females to one of five acoustic treatments: no stimulus, one of two irrelevant calls (conspecific chuck-only or heterospecific Physalaemus enesefae whine) or one of two behaviorally relevant calls (conspecific whine or whine-chuck). To determine the hypothalamic responses to these relevant and irrelevant calls, we examined mRNA levels of the activity marker egr-1 (also called krox-24, zif268, NGFI-A, TIS8, or ZENK) after acoustic stimulation (30). We measured egr-1 in seven hypothalamic nuclei (Fig.…”
mentioning
confidence: 99%
“…We processed brains of males for radioactive in situ hybridization to localize egr-1 mRNA, as previously described (Hoke et al, 2004;Hoke et al, 2007). We processed alternate sections of female brains, either for radioactive in situ hybridization against egr-1 or for TH immunocytochemistry, as follows.…”
Section: Tissue Processingmentioning
confidence: 99%
“…We used immediate-early gene egr-1 mRNA levels as a marker for neural (Hoke et al, 2004;Hoke, Ryan, & Wilczynski, 2005, and used immunohistochemistry for tyrosine hydroxylase (TH) protein as a marker for dopaminergic PT neurons. TH is an enzyme in the synthetic pathway shared by the catecholamines dopamine and norepinephrine.…”
Section: Introductionmentioning
confidence: 99%